2022
DOI: 10.1016/j.pec.2022.01.020
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on cancer patients, their carers and oncology health professionals: A qualitative study

Abstract: Objective Cancer patients, carers and oncology health professionals have been impacted by the COVID-19 pandemic in many ways, but their experiences and psychosocial responses to the pandemic are still being explored. This study aimed to document the experience of Australians living with cancer, family carers, and Oncology health professionals (HPs) when COVID-19 first emerged. Methods In this qualitative study, participants (cancer patients currently receiving treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…Patients, caregivers, and healthcare providers each experienced increased needs for psychological and spiritual supports during the pandemic, yet, reported suboptimal availability of these services, particularly in end-of-life circumstances [ 20 ▪▪ ]. Caregivers specifically desired more proactive mental health supports [ 24 ▪ ]. To address deficiencies, one specialty palliative care team leveraged the expertise of their chaplain and psychologist to offer telehealth to hospitalized patients and their caregivers with psychological and spiritual needs [ 11 ▪▪ ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Patients, caregivers, and healthcare providers each experienced increased needs for psychological and spiritual supports during the pandemic, yet, reported suboptimal availability of these services, particularly in end-of-life circumstances [ 20 ▪▪ ]. Caregivers specifically desired more proactive mental health supports [ 24 ▪ ]. To address deficiencies, one specialty palliative care team leveraged the expertise of their chaplain and psychologist to offer telehealth to hospitalized patients and their caregivers with psychological and spiritual needs [ 11 ▪▪ ].…”
Section: Resultsmentioning
confidence: 99%
“…The mental health crisis stemming from providing care during COVID-19 has been dubbed a ‘second pandemic’ [ 25 ], where an estimated 31–53% of healthcare providers have reported distress, anxiety, or depression in varying degrees [ 24 ▪ , 26 ], with nurses experiencing greater risk for these outcomes [ 27 , 28 ]. These estimates constitute a significant increase in psychological morbidity among healthcare providers from prior to the pandemic [ 28 , 29 ], and may stem from the demands of providing frequent end-of-life care [ 15 , 30 ], as well as moral distress over the inability to provide optimal care amid COVID-19 mitigation [ 31 ▪ , 32 ▪ ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a consequence, the pandemic induced a need for adapted criteria for SDM processes [ 10 ], but investigations aiming at patients’ attitudes towards SDM and predictors of decisional preferences during the pandemic are very rare [ 11 , 12 ]. For example, qualitative analyses by Edge et al [ 13 ] and Butow et al [ 14 ] showed pandemic-related SDM vulnerability of specific patient groups, such as in oncology, characterized by psychological distress, fear of virus susceptibility, practical issues in daily life, disruptions to treatment and services, information needs, and caregiver issues. In addition, various aspects of uncertainty as stressors for patients were identified [ 15 ].…”
Section: Introductionmentioning
confidence: 99%